ANALISIS TERJEMAHAN KALIMAT YANG MEREPRESENTASIKAN TUTURAN KESANTUNAN POSITIF DALAM NOVEL THE HOST KARYA STEPHENIE MEYER DAN DAMPAKNYA PADA KUALITAS TERJEMAHAN - Chairunnisa Chairunnisa; Djatmika Djatmika; Tri Wiratno (Universitas Sebelas Maret, 2016)
This research aims is to describe: (1) kinds of positive politeness markers in The Host novel, (2) translation techniques are used in the sentence that represent speech act of positive politeness in The Host novel, (3) the effects of the translation techniques which used by translators in sentences which represent politeness positive against the translation quality in terms of accuracy and acceptability.This research is a descriptive-qualitative research. The sources of data are the dialogues of The Host novel which represent positive politeness and also informants who assess the quality of the translation. Data were collected by the using analyzing of documents, questionnaires, and forum group discussion (FGD). Data are analyzed by using Spradley’s ethnography method.The result of this research shows that there are 15 kinds of positive politeness strategy markers on The Host novel. The most dominating positive politeness strategy of this data is sub-strategy of use in-group identity marker, as much as 22,49% of the data. In this research, the translation techniques consist of the application of single translation techniques as much as 102 times, 136 times as many as couplets varian, varian of triplets as many as 34 times, and varian of quartets 2 times. The translation quality from 263 data (95,64%) include as accurate translation and 12 data (4,36%) are less accurate translation, then 231 data (84%) includes as acceptable translation, and 44 data (16%) are less acceptable translation. The majority of translation techniques have contributed positively to translation quality of The Host novel.Keywords: positive politeness, translation tehniques, translation quality